Kazakh culture in the context of traditional civilizations of Eurasia (Journal of Philosophy Culture and Political Science, 2015)
This article is devoted to the place and role of Kazakh culture in the civilizational area of Eurasia. We consider the choice of models of socio-cultural development of the republic of Kazakhstan in the context of globalization and localization. identification of the kazakh culture is carried out in the context of its interactions with nomadic, muslim, Russian, Central Asian and East Asian civilizations. The role of cultural factors in the development of new post-soviet Central Asian states.Cultural imperialism is a losing position the same as cultural nationalism. Nationalism protrudes differences. Imperialism does not notice them. Nationalism on behalf of small cultures overly zealous on the part of sovereignty (autonomy, independence, authenticity).In fact imperialism is a nationalism on behalf of great culture which denies any recognition for small cultures. A way out was found in dialogue of cultures.Key words. Identification, eurasism, tradition and innovation, East and West, tolerance, civilization, nomadism, Islam.